Academic excellence as selection criteria among Malaysian employers - Hashim, Junaidah (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to examine whether or not performance of employees is determined by merit of their academic excellence, which is measured by cumulative grade point average (CGPA). This paper thus attempts to measure the variables that could possibly influence employees’ performance, such as job satisfaction, motivation and involvement in co-curriculum activities. Design/methodology/approach – An adapted version of the questionnaire used by Sarmiento et al. was utilised to assess the perceived performance of employees. Ability construct was measured in terms of employee academic qualification and skills. A 13-item scale based on Porter was used to measure motivation. A 14-item scale based on Hackman and Oldham’s Job Diagnostic Survey was used to measure job satisfaction. In total, 340 respondents from 87 companies participated in this study. Findings – The findings revealed that there is a weak relationship between employees’ performance with CGPA. The findings also revealed that there is a weak relationship between employees’ performance and their job satisfaction, motivation and ability. Research limitations/implications – It would be meaningful for future research if actual performance appraisal report could be obtained. Practical implications – Company policy makers need to provide a wider employment opportunity to everyone and not merely to candidates based on merit of their academic excellence. Many graduates may be missing out on employment opportunities while they may be the right candidates. Originality/value – This paper illustrates that academic excellence, which is the main selection criterion used by most employers, is not a determinant of employees’ performance.